The stone : a Persian legend of the Magi - Hofmeyr, Dianne (Farrar, Straus and Giroux, 1998)
A retelling of the story told to Marco Polo about the Magi of Saveh, three wise men from a town in Persia, who followed a strange star and find a special child.